Proximal tibia and tibial plateau nail-plate combinations: technical trick and case series - Yelena Bogdan, MD; Nicket Dedhia, MD (OTA International, 2022)
Abstract. Proximal tibia fractures and combined tibial shaft-plateau injuries are increasingly common. Prolonged nonweightbearing may result in poor outcomes, particularly in elderly patients. Nail–plate combination constructs offer an attractive solution to facilitate early weight-bearing in these complex problems. We describe strategies and tips for these constructs and present the results of a small patient series treated with this technique.